Substansi Penggunaan Metode Pembelajaran Pendidikan Agama Islam (Studi Kasus Di Kelas V SDN 18 Batang Anai) - Armalena, Armalena; Syahrizal (Universitas Yudharta Pasuruan, 2023)
This research aims to analyze the substance of the use of Islamic Religious Education learning methods in the context of basic education, focusing on a case study in Class V of SDN 18 Batang Anai. This research uses a qualitative approach with data collection techniques in the form of observation, interviews, and document analysis. The results showed that the use of lecture and question and answer methods in Islamic Religious Education subjects in Class V SDN 18 Batang Anai as a tool for learning activities with the aim of making learning easier for students to understand so that the learning process runs effectively. In this context, educators are still central in learning because they use lecture and question and answer methods. Communication that is fostered between educators and students makes the learning atmosphere more enjoyable and easily understood by students. This research provides insight into the substance of the use of Islamic Religious Education learning methods at SDN 18 Batang Anai, and its implications for the understanding and practice of Islamic religious values in students. The results of this study can be a reference for the development of more effective learning methods in the context of Islamic religious education at the primary level